Study Of Cerebrospinal Fluid Ferritin Level In Children With Meningitis (Journal of Pharmaceutical Negative Results, 2023)
Background: - Bacterial meningitis is still one of the significant causes of morbidity and mortality in children despite the use of antibiotics. Rapid diagnosis and differentiation between bacterial and aseptic meningitis is important for immediate antibiotic treatment in the former to prevent complications. Therefore, different tests have been developed for rapid diagnosis of bacterial meningitis. One of them is CSF ferritin, which is evaluated in this study. Aim: - study aimed to evaluate the cerebrospinal fluid ferritin levels in children with meningitis and differentiation between its bacterial and viral etiologies. Patients and Methods: This is a cross sectional comparative study included 50 children with a picture of suspected meningitis, 16 children ​diagnosed as bacterial meningitis, 17 children as viral meningitis, and 17 children as no meningitis attended the pediatric outpatient’s clinic and inpatient department of Kafr Elsheik Fever hospital. We include children with clinical suspicion of meningitis, while Children with CNS neoplasm, Children with irregular respiration, children who had deteriorating level of consciousness, Children with very recent siezures, traumatic CSF puncture or neurodegenerative diseases were excluded from the study. CSF ferritin level measurement was done by Eliza. Results: - Our results revealed that CSF ferritin level was statistically significant high in the bacterial group (92.69±36.62 ng/ml) when compared to those with viral (9.27±3.12 ng/ml), or no meningitis (6.31±2.94 ng/ml) groups. CSF ferritin showed a positive correlation with both serum CRP and CSF leucocyte in children with bacterial meningitis. The best cutoff point of CSF Ferritin for early differentiation bacterial from viral meningitis is ≥14.4 ng/ml with sensitivity of 100.00% and specificity of 100% with an area under the curve of 1.000 and (NPV) of 100% and (PPV) of 100%. Conclusion: - CSF ferritin levels were significantly elevated in patients with bacterial meningitis vs. aseptic meningitis. The differentiation of bacterial meningitis vs. aseptic meningitis by using CSF ferritin levels shown high specificity and sensitivity. Recommendation: We recommend to use CSF Ferritin as a useful biomarker in the early diagnosis of bacterial meningitis and to differentiate it from the viral one.